Synthesis and Characterization of some divalent transition metal complexes with acid hydrazone ligand - Bayan A. Faiq; Bayan O. Ahmed (Zanco Journal of Pure and Applied Sciences, 2021)
Complexes with the general formula [M(LH)2]X2 where M=Mn(II),Co(II),Ni(II) and Cu(II) LH= 4-acetylpyridine benzoyl hydrazone and X=chloride ion were synthesized. The structures were confirmed by IR spectroscopy, and characterized by elemental analyses, UV-vis, 1H.n.m.r 13C-n.m.r, and conductivity measurements. Molar conductance values in DMSO indicate that all complexes are electrolytes with mole ratio (1:2) and chloride ions not participate in coordination to central metal ion except Mn complex. The ligand act as bidentate, they coordinates through azomethine nitrogen (>C=N-) and carbonyl oxygen׳s.